Characterisation of some species groups of Brachymeria (Hymenoptera: Chalcididae), with a review of the B. tibialis-group and description of a new species parasitizing Zygaena pupae (Lepidoptera: Zygaenidae) - Delvare, Gérard; Shaw, Mark R. (Zootaxa, 2022)
The Brachymeria tibialis species group is newly recognized and diagnosed together with the Brachymeria annulata, femorata, kassiliensis and lasus species groups also newly defined. In these diagnoses a few morphological characters of the ventral part of the mesosoma, discovered in this study, are proposed to help differentiate the groups. The B. tibialis species group itself includes solely B. tibialis (Walker) and B. zygaenae Delvare & Shaw n. sp., which was until now mixed with it. The biology and hosts of both species are summarized.